(untitled) (Molecular Medicine Communications, 2022)
Paralysis after a spinal cord injury is due to the cut-off signaling between the brain and brainstem, especially those pathways that lead to a lumbar spinal cord. Kathe and her colleagues demonstrated that walking in nine patients with spinal cord injury significantly improved during the neurorehabilitation process in which the lumbar spinal cord’s spatiotemporal epidural electrical stimulation (EES) was used. A decrease in the lumber spinal cord neuronal activity was counterintuitively accompanied by improved human walking. The authors thought that this decrease in neuronal activity suggests the selection of a particular neuronal subpopulation essential for walking. To find this out, they recapitulated the same study in mouse models. They used transcriptomics and single-nucleus sequencing to chart the molecular circuitry of these mice from paralysis to recovery. They found a subset of neurons within the intermediate laminate. Interestingly, these neurons are not required for normal walking in healthy individuals, but the authors demonstrated that these neurons are essential for walking after a spinal injury. They further confirmed their findings by ablating these neurons, which prevented the recovery from a spinal injury, whereas augmenting these neurons further improved the recovery. The authors found a subset of neurons that organize the rescue of walking after spinal injury and provided a new framework for using molecular cartography to identify neurons required for certain behaviors. Nature (2022) DOI: https://doi.org/10.1038/s41586-022-05385-7.